Features of formation of competitive advantages of restaurants in the international markets - Yemchuk, Tetiana; Arpul, Oksana (VUZF Publishing House “St. Grigorii Bogoslov”, 2019)
Every year in the world there is a large number of new food establishments very diverse in their characteristics and methods of service. Chefs and restaurateurs must constantly come up with something new and unusual to attract customers. Every year the restaurant industry is being modernized, refined and expanded, offering new dishes, approaches to production and conceptual ideas for a variety of food establishments.
Features of formation of competitive advantages of restaurants in the international markets
Keywords: restaurant business; restaurant industry; competitiveness